RESTRUKTURISASI KETENAGAKERJAAN DALAM PROSES MODERNISASI BERDAMPAK PERUBAHAN SOSIAL PADA MASYARAKAT PETANI - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006, 2012)
Sugar, one of the commercial plant state commodity for Indonesia; which are the necessary for human being, under any circumstances. But, sugar cane cause the land more tight to get rid of these difficult problems, by conducting “Tebu Rakyat Intensifikasi” programs. These purpose of research, to know about the labor concerning income, trend, and the restructurization become of labor transformation, which were depended the social change on social, economics, culture and politics trend of the sugar cane peasant, at Langkat and Deli Sedang districts, North Sumatera. “P.G” Kuala Madu is the cane industry manufactory, which the “TRI” program’s applied. The labor interaction caused the many social change problems. : “Social change is the significant alteration of social structure through time”. “Social structure means a persistent network of social relationships in which interaction gas become routine and repetitive”. (Harper, 1989). Sugar cane farming system, to increasing sugar cane productivity and farmer (peasant) incomes by “TRI” policy program, and aspect of it for competitive influence ability and sugar selling price in international market and domestic market. The identifying problems of sugar factory such BUMN’s inefficiency ; institution infractions, the weakness or dilated of governance to anticipatory the implication of many other sugar cane problem. Aim, the restructurization on labor of sugar cane farmers need government attended and, the restructurization of sugar factory should be directed to share owning removement to farmers of sugar cane.
Keywords: Labor Restructuring, Modernization Process, Social Change, and Peasant Community